PROTOTYPE LAYANAN IZIN PEMANFAATAN RUANG UNTUK AKOMODASI PARIWISATA MENGGUNAKAN SERVICE ORIENTED ENTERPRISE ARCHITECTURE FRAMEWORK (Studi Kasus Kantor Pelayanan Perizinan Terpadu Kabupaten Karangasem) - , Desak Putu Juniati; , Ir. Lukito Edi Nugroho, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
When people make a discussion about license registration process, they usually give focus only on the integrated service that put all the included services together in one place. While in fact, on the other hand, there are vital aspects that are not yet handled properly regarding the information presentation served to people in need. The people served in this discussion are those who need the information about land availability and its appropriate use related to the regulation established. The objective of this research is to create the prototype for the service of land using permit (Izin Pemanfaatan Ruang), especially for tourist accommodation business, which the registration service is carried out in The License Registration Office of Karangasem Regency. This prototype consists of two main services that are the service presented in front office and the service presented in back office. The front office service is presenting the land availability information service and the land using for tourist accommodation registration service. While the back office service is presenting data processing service and the license issuing service. The front office service prototype is presenting the service on the information about spatial and attribute data related to the land ownership and land use blocking regulation. The information about the land ownership is given by conducting an integrated service with The National Land Office of Karangasem Regency, while the information about the land use blocking regulation is given by conducting an integrated service with The Development Planning Office of Karangasem Regency. The research is carried out by using the approach of Service Oriented Enterprise Architecture Framework (SOEAF), which integrates Service Oriented Architecture (SOA) into the framework of Enterprise Architecture. The integration is conducted by using the extension of Zachman framework which adding a new column named service column consisting contextual level, conceptual level, logical level and physical level. The prototype is evaluated by using the black box testing approach based on the case given. The result of the evaluation shows that the prototype service on the land using permit registration, especially for the tourist accommodation, which is having an interoperability data with The National Land Office of Karangasem Regency and The Development Planning Office of Karangasem Regency is able to give more correct information and assurance to the users.